Menganalisis penerapan nilai tauhid dalam pembentukan karakter dan kurikulum Islam dalam konteks ketuhanan - Abdan Syakuro; Abdul Khobir; Sasa Refiatul Alfianti; M. Fajrul Falah (Jurnal Pendidikan Agama Islam, 2026)
The value of monotheism is the main foundation in Islamic teachings, which emphasizes the oneness of Allah SWT as the center of all spiritual and social life of a Muslim. In the context of adolescents transitioning from childhood to adulthood, this is a crucial phase in the formation of identity and religious beliefs. Education in schools that emphasizes the value of monotheism in learning can help adolescents who are searching for their identity to avoid being influenced by things that are not in accordance with religious norms. The Islamic education curriculum is not only oriented towards cognitive aspects, but also on the formation of personality and morals based on the values of tauhid. This study aims to examine and analyze the application of tauhid values in character building and Islamic curriculum in the context of divinity, in order to determine the extent to which the application of tauhid values in character building and curriculum can be implemented in life.